2022
DOI: 10.1111/1471-0528.17180
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional diagnostic accuracy study of self‐testing for proteinuria during hypertensive pregnancies: The UDIP study

Abstract: Objective: To determine the accuracy of self-testing for proteinuria during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Home blood pressure monitoring both during pregnancy and postpartum has been demonstrated previously to be feasible and acceptable to pregnant and postpartum individuals 35–37 . Recent data also support the use of home monitoring for proteinuria during pregnancy, which may be particularly useful when incorporated into remote approaches to antenatal care 38 …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Home blood pressure monitoring both during pregnancy and postpartum has been demonstrated previously to be feasible and acceptable to pregnant and postpartum individuals 35–37 . Recent data also support the use of home monitoring for proteinuria during pregnancy, which may be particularly useful when incorporated into remote approaches to antenatal care 38 …”
Section: Discussionmentioning
confidence: 89%
“…[35][36][37] Recent data also support the use of home monitoring for proteinuria during pregnancy, which may be particularly useful when incorporated into remote approaches to antenatal care. 38 Despite promising data in the non-pregnant population, few studies have investigated self-monitoring of BP combined with additional support. Our study suggests a modest lowering of blood pressure in the intervention arms.…”
Section: Mean (95% Ci) or Median [Iqr]mentioning
confidence: 99%
“…At present, test strips are used for a quick and simple diagnosis of proteinuria, easy to handle and apply both by primary health personnel in a prenatal consultation, and for use by the patient at home [30]. Although they can give results as false positives or negatives, motivated by the fact that the presence of pathologies prior to pregnancy or not must be known, it is useful in patients with blood pressures of 140/90 mmHg, for monitoring at home, which allows go to a care center if they are positive [30].…”
Section: Usefulness Of Urinementioning
confidence: 99%
“…Early work from small observational studies suggested the potential for reduced morbidity and resource use, as well as acceptability and feasibility, yet evidence from large-scale randomised trials for the effectiveness of SMBP in pregnancy has been lacking until recently [ 7 9 ]. This article reviews the findings from the Blood Pressure Monitoring in Pregnancy (BUMP) programme of work, undertaken in the United Kingdom (UK), in this rapidly developing area [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the study also showed that automated colorimetric testing was not significantly different to performance by women or healthcare professionals. Although the accuracy of urine dipstick testing is not as high as desired in a diagnostic test, testing in the context of antenatal care, which includes repeated testing, is likely to be beneficial [ 13 ]. Furthermore, using protein testing in combination with home BP monitoring could allow better reassurance to both healthcare professionals and women that the important indicators of evolving pre-eclampsia are being monitored.…”
Section: Introductionmentioning
confidence: 99%